Effect of an 8-week strength training program on ankle flexibility and explosive strength following fibula fracture: a case study of a female vaulting athlete - Smoliga, J. E.; Hajduová, K.; Vavák, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Returning to training post-injury presents challenges, especially with mobility restrictions in affected musculoskeletal areas. METHODS: This study aimed to assess the effects of lower limb 8-week strength training program on fitness and angle parameters post-fibula fracture rehabilitation of a 22.2-year-old female. Exercises were divided into three groups: main, supplementary, and compensatory. Input diagnostics of 6 RM in main exercises gradually increased load from 50% of 1RM to 90-95% of 1RM during the 8-week program. Trainings were performed 3 times a week. Parameters included maximum isometric strength (FMAX) in the 90° back squat, ankle angular range (ROM), and bilateral and unilateral countermovement jump (CMJ) were measured every week during baseline and intervention. Ankle angular range was measured using the TiltMeter app for the weight-bearing lunge test. FMAX was measured using FiTRO Force desk and CMJ was measured using OPTOJUMP next. Statistical analysis utilized non-parametric C analysis for single-subject research design for assessing elite athletes. RESULTS: Bilateral CMJ improved by 9.6 cm from a baseline of 35.9 cm to 45.5 cm after intervention, with statistical significance at the 1% level (C = 0.752). Unilateral CMJ of the left lower limb improved from a baseline of 19.5 cm to 23.9 cm after intervention, and the right lower limb improved from a baseline of 15.8 cm to 23.4 cm after intervention. The discrepancy between left and right lower limb CMJ reduced from 3.7 cm to 0.5 cm. ROM of the left ankle increased by 8.7° and ROM of the right ankle increased by 18.3° during the strength mesocycle, with a statistically significant improvement in the right lower limb at the 1% level (C = 0.819). FMAX in the back squat showed a significant increase from a baseline of 2036.3 N to 2391.1 N after intervention, with statistical significance at the 5% level (C = 0.500). CONCLUSION: Our study demonstrates the effectiveness of targeted lower limb strength training in improving fitness and angle parameters during fibula fracture rehabilitation. These findings underscore the importance of incorporating strength-focused interventions to optimize recovery outcomes and facilitate return to physical activity post-injury.